2004
DOI: 10.1007/s10342-004-0017-7
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatological regions of Douglas fir ( Pseudotsuga menziesii Franco) in western Poland

Abstract: Six Douglas fir (Pseudotsuga menziesii Franco) stands were selected in both the Sudety Mountains and the Great Poland Lowland. These two regions are distinctly different with regard to thermal and pluvial conditions. In each stand, two increment cores per tree were extracted from 20 approximately 100-year-old trees and the tree-ring widths measured. It is clear from the different growth reactions of the study trees to the climatic conditions that the Sudety Mountains and the Great Poland Lowland are two dendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…It should be mentioned that research concerning this species hitherto, and confirmed during this study, have indicated that air temperature of winter is the main factor similarly modeling magnitude of tree diameter increment in the entire area of Poland (Feliksik and Wilczyński, 1998a,b, 2002a, 2003a,b, 2004. This is the strongest climatic signal embedded in Douglas fir tree-rings.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It should be mentioned that research concerning this species hitherto, and confirmed during this study, have indicated that air temperature of winter is the main factor similarly modeling magnitude of tree diameter increment in the entire area of Poland (Feliksik and Wilczyński, 1998a,b, 2002a, 2003a,b, 2004. This is the strongest climatic signal embedded in Douglas fir tree-rings.…”
Section: Discussionsupporting
confidence: 75%
“…3). This confirmed a known phenomenon of an inverse relationship between the chronology similarity and the distance between them (Müller-Stoll, 1951;Ermich, 1960;Feliksik, 1990;Zielski, 1997;Feliksik and Wilczyński, 1996, 2003aWilczyński and Skrzyszewski, 2002a). There were, however, cases when site chronologies did not show statistically significant similarity (Fig.…”
Section: Forest Districtsupporting
confidence: 75%
See 1 more Smart Citation
“…Dendroecological studies report that summer precipitation influences the increment of Douglas-fir in lowland, western Poland (Feliksik and Wilczynski, 2004) whereas radial growth of beech at low altitudes in continental climate (Dittmar et al, 2003) and in coastal climate (van der Werf et al, 2007) appears to be relatively insensitive to summer water shortage. In a central European context we define drought as a day or a sequence of days where the plant water demand exceeds plant available water.…”
Section: Introductionmentioning
confidence: 99%
“…July droughts adversely affected the length of the shoots and tree ring widths in the trees, and so high rainfall in July, amounting to 126% of normal, significantly positively influenced the annual growth of black locust in the years 1955-2014, and contributed to its proper growth. Literature gives various limits for pointer years, usually ranging from 60% to 90% of trees (Feliksik & Wilczyński 2004;Poljanšek et al, 2012). The threshold value depends, among others, on the tree species, location, or the size of the tested sample (Wilczyński, 2004;Wilczyński & Szymański 2014).…”
Section: Discussionmentioning
confidence: 99%